2022
DOI: 10.3389/fmicb.2022.939904
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Daqu on Microbial Community Domestication and Metabolites in Nongxiang Baijiu Brewing Microecosystem

Abstract: The quality and yield of the fresh Baijiu mainly depend on the activity of pit mud (PM) and the quality of Daqu. However, the cultivation of PM is a long-term process, and high-quality Daqu can change the community structure of fermented grain (FG) and accelerate the evolution of PM communities. The present research aimed to investigate the four different types of Daqu on the FG-fermenting microbial community structure and metabolites and their interphase interactions with PM. These results show that Kroppenst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…6 c (E vs C) showed that a total of 19 different phenolic metabolites were identified in fermented grains before koji mixing and after the mixing of Daqu , of which 6 were up-regulated and 13 were down-regulated. It was possible that the mixing of Daqu down-regulated a large parts of phenolic metabolites, because Daqu was mainly a collection of beneficial microbial communities and contained a very small number of phenolic substances ( Mao, Huang, Zhou, et al, 2022 ). Fig.…”
Section: Results and Analysismentioning
confidence: 99%
“…6 c (E vs C) showed that a total of 19 different phenolic metabolites were identified in fermented grains before koji mixing and after the mixing of Daqu , of which 6 were up-regulated and 13 were down-regulated. It was possible that the mixing of Daqu down-regulated a large parts of phenolic metabolites, because Daqu was mainly a collection of beneficial microbial communities and contained a very small number of phenolic substances ( Mao, Huang, Zhou, et al, 2022 ). Fig.…”
Section: Results and Analysismentioning
confidence: 99%
“…Many studies in the past decade have focused on microbial distributions and the factors influencing the micro-ecosystem of baijiu brewing. 3,8,[27][28][29][30] However, few of them have evaluated the impact of seasonal variations on microbial communities, physicochemical indices, and VFCs in the SFB fermentation system. 22 In this study, we investigated the diversity and assembly of microbes presented in the ZP used for SFB production across four seasons, as well as their correlations with environment variables.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bacillus and Acetobacter are positively correlated with forming acetate esters, while Lactobacillus is significantly associated with lactic acid 5 . Kroppenstedtia is positively correlated with ethyl caproate, 8 and Caproiciproducens , Syntrophaceticus , Sedimentibacter , Hydrogenispora , Pelotomaculum , and Bacillus notably affected the production of hexanoic acid 9 …”
Section: Introductionmentioning
confidence: 99%
“…Since the fermentation process is carried out in an open environment, the structure of Daqu microbiota can be easily affected by raw materials (Zhang et al., 2022 ), environmental factors (e.g., tools, indoor ground, room temperature) (Li et al., 2016 ; Zhang et al., 2022 ) and fermentation technology (e.g., ventilation, packing method) (Kang et al., 2022 ), resulting in different Daqu types. Recent studies have revealed that fermenting Daqu with different raw materials leads to varying microbial characteristics (Mao et al., 2022 ). Daqu ‐making environments, such as indoor ground and tools, are the main sources of fungal communities in Daqu , while raw materials primarily contribute to bacterial communities (Du et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%